2009
DOI: 10.1021/bi900569h
|View full text |Cite
|
Sign up to set email alerts
|

A New Function of GAPDH from Chlamydomonas reinhardtii: A Thiol−Disulfide Exchange Reaction with CP12

Abstract: CP12 is a flexible protein that is well-known to interact with GAPDH, and this association is crucial to the regulation of enzyme activity. This regulation is likely related to structural transitions of both proteins, but the molecular bases of these changes are not yet understood. To answer this issue, we undertook a study based on the use of paramagnetic probes grafted on cysteine residues and followed by EPR spectroscopy. We present a new application of this approach that enables us to probe the functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 39 publications
1
27
0
Order By: Relevance
“…Peptide mass fingerprints were also obtained after tryptic digestion of wtSAL3 and rec(ÀHis)SAL3, using the above mass spectrometer [56]. The proteins digested were studied by performing one-dimensional liquid chromatography (Finnigan Surveyor HPLC Pumps) combined with an ion trap LCQ-DECA XP mass spectrometer (Thermo Finnigan), as previously described [57].…”
Section: Post-translational Modification Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Peptide mass fingerprints were also obtained after tryptic digestion of wtSAL3 and rec(ÀHis)SAL3, using the above mass spectrometer [56]. The proteins digested were studied by performing one-dimensional liquid chromatography (Finnigan Surveyor HPLC Pumps) combined with an ion trap LCQ-DECA XP mass spectrometer (Thermo Finnigan), as previously described [57].…”
Section: Post-translational Modification Hypothesismentioning
confidence: 99%
“…The proteins digested were studied by performing one-dimensional liquid chromatography (Finnigan Surveyor HPLC Pumps) combined with an ion trap LCQ-DECA XP mass spectrometer (Thermo Finnigan), as previously described [57]. The peptides generated upon trypsin hydrolysis and identified by mass spectrometry were superimposed on the theoretical trypsin cleavage map [56] (Fig. 7).…”
Section: Post-translational Modification Hypothesismentioning
confidence: 99%
“…(3) Recent analysis of genome data from 126 species of cyanobacteria has revealed a wide diversity of CP12 protein sequences raising questions about the role of these different CP12 and CP12-like proteins (Stanley et al, 2013). (4) CP12 is a member of a class of proteins known as intrinsically unstructured proteins (IUPs; Gardebien et al, 2006; Erales et al, 2009b; Mileo et al, 2013). This article presents brings together information from a number of recent studies that suggest that CP12 may have a broader role in the regulation of metabolism, over and above the well established role of CP12 in the regulation of the Calvin–Benson cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Structural and in silico studies have demonstrated that CP12 has physicochemical properties similar to those of IUPs (Graciet et al, 2003; Gardebien et al, 2006; Erales et al, 2009b; Marri et al, 2010; Mileo et al, 2013). IUPs possess relatively little structure in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…In the green alga C. reinhardtii, CP12 and GAPDH have complex interactions centered on the Cys pairs. GAPDH can undergo a thiol-disulfide exchange reaction with CP12, cleaving the C-terminal disulfide bond (Erales et al, 2009c). CP12 has also been shown to regulate the Calvin cycle in a redox-independent manner, acting as a specific chaperone for GAPDH to prevent thermal inactivation and aggregation (Erales et al, 2009b).…”
mentioning
confidence: 99%